+0  
 
0
38
2
avatar

Factor by grouping: 9x^4+9x^3+27x+27

 Sep 28, 2020
 #1
avatar+10336 
+1

Factor by grouping: 9x^4+9x^3+27x+27

 

Hello Guest!

 

 

adoption \(x_1=-1\)

 

  (\(x^4\) +  \(x^3\)+3x+3) : (x+1) = \(x^3+3\)

  \(\underline{x^4+x^3}\)

             0 \(3x+3\)

                \(\underline{3x+3}\)

                          0

\(x^3+3=0\\ x_{2,3,4}=\sqrt[3]{-3} =-1.4422\)

 

 

 

Factor by grouping: \(9x^4+9x^3+27x+27\) = \(9\times (x+1)\times (x-\sqrt[3]{-3})^3\)

laugh  !

 Sep 29, 2020
edited by asinus  Sep 29, 2020
edited by asinus  Sep 29, 2020
 #2
avatar
0

\(\displaystyle 9x^{4}+9x^{3}+27x+27 \\ = (9x^{4}+27x)+(9x^{3}+27) \\ =9x(x^{3}+3)+9(x^{3}+3) \\ = 9(x^{3}+3)(x+1).\)

.
 Sep 29, 2020

24 Online Users

avatar